Optimizing Organizational Justice and Emotional Intelligence to Mitigate Counterproductive Work Behavior - Musdalifa, Musdalifa; Iskandar, Ahmad Syarief; Taqwa, Taqwa (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
This study explores the impact of organizational justice and emotional intelligence on counterproductive work behaviour at SMPIT Insan Madani, aiming to identify their individual and collective influences. Utilizing a quantitative ex-post facto approach, the research encompasses all 33 educators at SMPIT Insan Madani, employing probability sampling for equitable participant selection. Data collection relied on questionnaires and documentation, analyzed using SPSS version 20 for descriptive and inferential statistics. Findings revealed a significant relationship between organizational justice and counterproductive work behaviour, highlighted by a t-value of 35.023 and a significance level below 0.025. Emotional intelligence also significantly affected counterproductive behaviours, as evidenced by a t-value of 1.896 with a significance below 0.025. Furthermore, the combined effect of organizational justice and emotional intelligence on such behaviours was statistically significant, indicated by an F-value of 125.640, exceeding the F-table value of 2.922, and a significance level above 0.05. A high coefficient of determination (94.5%) suggests these factors are pivotal in influencing counterproductive work behaviour at SMPIT Insan Madani, underscoring the importance of fostering a just organizational environment and enhancing emotional intelligence to mitigate negative workplace behaviours.